2011
DOI: 10.1186/1471-2458-11-802
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet use in Chinese adolescents and its relation to psychosomatic symptoms and life satisfaction

Abstract: BackgroundProblematic Internet use (PIU) is a growing problem in Chinese adolescents. Little is known about associations of PIU with physical and psychological health. This study was designed to investigate the prevalence of PIU and to test the relationships between PIU and psychosomatic symptoms and life satisfaction among adolescents in mainland China.MethodsA cross-sectional survey was conducted comprising a large representative sample of 17 599 students in eight cities of China. PIU was assessed by the 20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
231
7
35

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(303 citation statements)
references
References 42 publications
30
231
7
35
Order By: Relevance
“…In addition to the prevalence estimates reported, the studies have found that in adolescents, Internet addiction is associated with the following sociodemographic variables: higher family income levels [61,63], male gender [45, 61-63, 65, 66, 81, 83], female gender [48], being left behind (i.e., abandoned), and migrant [68], living in rural areas [81], being in senior high school, and having a monthly spending over 100 RMB [45]. The discrepancy between findings concerning associations between Internet addiction and gender can possibly be explained by the measures utilised, i.e., Liu et al [48] found that a higher percentage of girls reports excessive usage behaviours, which might be indicative of their increased problem awareness relative to boys.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the prevalence estimates reported, the studies have found that in adolescents, Internet addiction is associated with the following sociodemographic variables: higher family income levels [61,63], male gender [45, 61-63, 65, 66, 81, 83], female gender [48], being left behind (i.e., abandoned), and migrant [68], living in rural areas [81], being in senior high school, and having a monthly spending over 100 RMB [45]. The discrepancy between findings concerning associations between Internet addiction and gender can possibly be explained by the measures utilised, i.e., Liu et al [48] found that a higher percentage of girls reports excessive usage behaviours, which might be indicative of their increased problem awareness relative to boys.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…A total of seven studies used the IAT for Internet addiction assessment in adolescents and children aged 8 to 24 years [61][62][63][64][65][66][67], with sample sizes ranging from 1,618 [65] to 17,599 participants [63]. Although the same measurement instrument has been used in these studies, various cut-offs have been applied to demarcate addiction or excessive use across studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
“…Cross-sectional pen-and-paper survey Modified Minnesota Impulsive Disorder Inventory (Grant et al, 2005), endorsing craving, withdrawal, and abstinence attempts simultaneously indicates problematic Internet use 4% with problematic Internet use Cao et al (2011) To investigate the prevalence of problematic Internet use (PIU) and its relationships with psychosomatic symptoms and life satisfaction among adolescents in mainland China N = 17,599 adolescents in China sampled via stratified cluster sampling in schools (mean age = 16.1 years) School-based cross-sectional survey Young's Internet Addiction Test (Young, 1999), scoring >50/100 indicates addiction 8.1% with problematic Internet use Park et al (2008) To explore relations between risk and protective factors and Internet among adolescents in South Korea N = 903 middle and high school students in South Korea (60.5% middle school seniors, 39.5% high school students (12.4% freshman, 27.1% juniors)) randomly selected from schools in Seoul Cross-sectional pen-and-paper survey Modified Young's Internet Addiction Scale (IAS) (1998), scoring ≥70 indicates addiction 10.7% addicted Müller et al (2012) To explore Internet addiction prevalence in a clinical context in Germany N = 81 child and adolescent psychiatric patients in Germany (mean age = 13.6 years)…”
mentioning
confidence: 99%
“…Third, the problem user could be categorized by combining two common types of user that cause concern, namely the at-risk and addicted populations. 34,44,57,62 Fourth, one could select dependent and nondependent individuals using the mean (M) -½ standard deviation (SD). 32 Finally, the categorization could be obtained through multivariate statistical analyses, such as cluster analysis.…”
mentioning
confidence: 99%